Trypanosome population biology - an approach to support the control of drug resistance and integrated trypanosomosis control - Coleman, P.G.; McDermott, John J. (European Union, 2000)
The identification and tracking of sub-populations through time and space are critical to fully understanding the epidemiology of parasitic diseases. However, very little is known about the structure, distribution and dynamics of trypanosome populations in the field. Most laboratory studies that have characterised trypanosomes have concentrated on adapted clones, while in those studies that have applied the characterisation techniques to field samples the number of isolates examined tended to be relatively small. Here, we examine how knowledge of the population biology of trypanosomes could be used to better understand the epidemiology of drug resistance and inform the design of integrated control strategies to manage the spread of drug resistance. Specific areas of research are proposed (e.g. experimental determination of the relative fitness of drug-sensitive and drug-resistant clones) that are important to furthering this knowledge.